1999
DOI: 10.1177/096368979900800107
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporine A-Induced Hyperactivity in Rats: Is it Mediated by Immunosuppression, Neurotrophism, or Both?

Abstract: Cyclosporine A (CsA) immunosuppressive treatment has become an adjunctive therapy in neural transplanta tion of dopamine-secreting cells for treatment of Parkinson's disease (PD). Recently, CsA and its analogues have been shown to promote trophic effects against neurodegenerative disorders, and therefore CsA may have direct beneficial effects on dopaminergic neurons and dopamine-mediated behaviors. The present study examined the interaction between the reported CsA-induced hyperactivity and the possible altera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…After the infusion, all animals were injected with cyclosporin A daily (10 mg/kg intraperitoneally). Because cyclosporin has neuroprotective activity in MCAO, 12 animals that did not receive HUCBC were also injected daily with cyclosporin A.…”
Section: Transplantation Of Hucbcmentioning
confidence: 99%
“…After the infusion, all animals were injected with cyclosporin A daily (10 mg/kg intraperitoneally). Because cyclosporin has neuroprotective activity in MCAO, 12 animals that did not receive HUCBC were also injected daily with cyclosporin A.…”
Section: Transplantation Of Hucbcmentioning
confidence: 99%
“…Because the mechanism by which cyclosporine induces hypertension is not well defined. In addition, recent studies have shown that cyclosporine plays a neuroprotective role (Friberg et al, 1998) , as well as trophic effects (Borlongan et al, 1999) and modifies behavioral activity in normal animals and models. Humans who have diseases of the neurodegenerative disorder (Tomac et al, 1999) .…”
Section: Introductionmentioning
confidence: 99%